Studies of charm and beauty hadron long-range correlations in pp and pPb collisions at LHC energies - CMS Collaboration; Damarseçkin, Serdal (ELSEVIER, 2021)
Measurements of the second Fourier harmonic coefficient (v(2)) of the azimuthal distributions of prompt and nonprompt D-0 mesons produced in pp and pPb collisions are presented. Nonprompt D-0 mesons come from beauty hadron decays. The data samples are collected by the CMS experiment at nucleon-nucleon center-of-mass energies of 13 and 8.16 TeV, respectively. In high multiplicity pp collisions, v(2) signals for prompt charm hadrons are reported for the first time, and are found to be comparable to those for light-flavor hadron species over a transverse momentum (pT) range of 2-6 GeV. Compared at similar event multiplicities, the prompt D-0 meson v(2) values in pp and pPb collisions are similar in magnitude. The v(2) values for open beauty hadrons are extracted for the first time via nonprompt D-0 mesons in pPb collisions. For pT in the range of 2-5 GeV, the results suggest that v(2) for nonprompt D-0 mesons is smaller than that for prompt D-0 mesons. These new measurements indicate a positive charm hadron v(2) in pp collisions and suggest a mass dependence in v(2) between charm and beauty hadrons in the pPb system. These results provide insights into the origin of heavy-flavor quark collectivity in small systems. (C) 2020 The Author(s). Published by Elsevier B.V.
Keywords: CMS; Ridge; Collectivity; Small systems; Heavy flavor; Elliptic flow